Investigating Google Sites in the intensive and extensive listening classroom in EFL context: Implementation and students - Ruswandi, Syilva Adisty; Purnawarman, Pupung; Gunawan, Muhammad Handi (Journal on English as a Foreign Language, 2024)
Numerous scholarly investigations have been conducted on students' perceptions of implementing Google Sites in various learning environments, including English as a foreign language (EFL) context. However, some existing research lacks specific exploration of the use of Google Sites in both intensive and extensive listening classrooms in tertiary education. This study aims to investigate the implementation of Google Sites in that specific listening classroom. This case study involved twenty-two first-year students in English language education at one of the public universities in Bandung, Indonesia. Data were collected through classroom observation, students' reflection, and semi-structured interviews, and they were analyzed thematically using NVivo as a helping tool. Results indicate that, according to the implementation and the ease of using Google Sites in their listening classroom, students generally hold positive attitudes towards Google Sites, finding it beneficial to improve their listening skills along with their creativity. Conversely, some students experience challenges that evolve around poor internet connectivity, accessibility, and adjustability of the website. This study promotes Google Sites as an alternative learning tool to assist both teachers and students in meeting their learning objectives in a fun and creative way.